Arbuscular mycorrhizal fungi and phosphorus supply accelerate main medicinal component production of Polygonum cuspidatum - Sun, Rui-Ting; Zhang, Ze-Zhi; Liu, Ming-Yang; Feng, Xiang-Cao; Zhou, Nong; Feng, Hai-Dong; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Harsonowati, Wiwiek; Wu, Qiang-Sheng (Frontiers in Microbiology, 2022)
The medicinal plant Polygonum cuspidatum Sieb. Et Zucc is rich in stilbenes (e.g., polygonin and resveratrol) and anthraquinones (e.g., emodin) for the therapy of human diseases, while how to increase the growth and medicinal composition concentrations of P. cuspidatum has become an urgent issue. The aim of the present study was to evaluate effects of inoculation with an arbuscular mycorrhizal (AM) fungus, Funneliformis mosseae, on plant growth, phosphorus (P) acquisition, medicinal component concentrations, and expressions of resveratrol synthesis-associated enzyme genes of P. cuspidatum at two P levels (0 M and 0.2 M). P supply (0.2 M) stimulated root AM fungal colonization rate. F. mosseae inoculation significantly improved growth performance (height, diameter, and biomass) and root morphology (diameter, length, and projected area), irrespectively of substrate P levels. P supply and F. mosseae distinctly increased soil acid and neutral phosphatase activities, as well as root P concentrations. P supply increased root physcion and resveratrol concentrations in inoculated and uninoculated plants, along with up-regulated expressions of PcCHS1, PcCRS1, PcRS11, and PcSTS. AM plants represented significantly higher root aleo-emodin, chrysophanol, emodin, physcion, polydatin, and resveratrol concentrations than non-AM plants irrespective of P levels, coupled with up-regulated expressions of PcCHS1, PcCHS2, PcRS11, PcRS, and PcSTS. It is concluded that 0.2 M P supply and F. mosseae inoculation promoted chrysophanol, physcion, polydatin, and resveratrol concentrations of P. cuspidatum, with the increase in resveratrol associated with up-regulated expressions of related genes.